Correlation Analysis of Lactic Acid Level as A Predictor of Severity of Patients with Acute Appendicitis (Majalah Kedokteran Bandung, 2023)
Perforated appendicitis is a leading cause of morbidity and mortality in all appendicitis cases, both for adults and children. Delay in preoperative diagnosis is the main reason for perforation. In previous studies, it was revealed that diagnostic modalities such as radiological examination and the current scoring system have not been able to predict the onset of perforated appendicitis. Serological biomarkers of lactic acid are associated with intestinal obstruction and ischemia. The increase in the serological value of lactic acid in perforated appendicitis compared to acute one was shown to increase significantly by 0.25 mmol/L (p
Keywords: Correlation; lactic acid; perforated appendicitis